2023
DOI: 10.1002/adtp.202300005
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Viral Nucleic Acid Delivery System for RNA Therapeutics

Abstract: Nucleic acid drugs can treat diseases caused by defective or abnormal genes. Herein, the mechanism of non‐viral vectors for nucleic acid drug delivery is described. This review introduce non‐viral vectors for nucleic acid drug delivery, including the nucleic acid‐carrier conjugate, proteins and peptides‐based nanoparticles, polysaccharides, and other biological macromolecules‐based nanoparticles consisting of lipid nanoparticles, synthetic polymers‐based nanoparticles, inorganic nanoparticles, and organic–inor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 249 publications
0
4
0
Order By: Relevance
“…The CPCs are well soluble (>5 mg/mL) in alcohol and PBS buffer (20 mM, pH 7.4). 1 H NMR spectrum analysis (Figure 2a) indicated that the chemical shifts of the CPCs were in good agreement with their chemical structures. Moreover, no signals at δ 1.5 ppm, corresponding to the protons of the boc-protecting group, were observed, suggesting complete removal of this group.…”
Section: Preparation and Characterization Of Cpcs As Nonviral Gene Ca...mentioning
confidence: 65%
See 3 more Smart Citations
“…The CPCs are well soluble (>5 mg/mL) in alcohol and PBS buffer (20 mM, pH 7.4). 1 H NMR spectrum analysis (Figure 2a) indicated that the chemical shifts of the CPCs were in good agreement with their chemical structures. Moreover, no signals at δ 1.5 ppm, corresponding to the protons of the boc-protecting group, were observed, suggesting complete removal of this group.…”
Section: Preparation and Characterization Of Cpcs As Nonviral Gene Ca...mentioning
confidence: 65%
“…The THP-PNC product was purified on a silica column with DCM as a dilute and obtained as a solid powder after solvent evaporation (yield: 0.33 g, 32%). The monomers were characterized by 1 1b). As a procedure for the synthesis of BHE-BAP, BHE-PNC (0.83 g, 1.5 mmol) and BAP (0.31 g, 1.5 mmol) were dissolved in anhydrous DMF (2 mL) as a solvent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations